Business characteristics and leadership motivation in circular economy practices: a case study of small manufacturers in Dallas-Fort Worth - Howe, Kate; Lavy, Brendan L. (Frontiers in Sustainability, 2025)
The circular economy (CE) provides an operational framework for businesses to reduce environmental impacts and achieve sustainability goals. Businesses are increasingly integrating CE practices into their operations; however, implementation varies by industry, business type, and size. Globally, small and medium sized businesses constitute the majority of all businesses, and their aggregated environmental impacts outweigh those of larger businesses. Small manufacturers, in particular, produce more pollution than other industries, and their shift to more sustainable practices aligned with the CE affects regional-to-local environmental conditions. Despite their significance, less is known about the CE practices of small and medium-sized businesses, particularly those of small manufacturers. We distributed a survey to small manufacturers across Dallas-Fort Worth and received 69 valid responses from an initial list of 4,320 contacts for a survey response rate of 1.6%. We documented their use of CE practices and assessed the extent to which their leadership’s motivation toward the environment and company characteristics influence the adoption of practices. Our resu.lts showed the adoption of CE practices by small manufacturers increased with stronger leadership motivation and was influenced by company characteristics. We found that disadvantaged manufacturers implemented more resource optimization practices than their non-disadvantaged counterparts, potentially reflecting social responsibility, supply chain pressures, or differentiation strategies. Environmental certifications were the most consistent indicator of broader CE adoption, particularly in product design, material sourcing, and waste management. Manufacturers with annual sales revenue above $10 M also demonstrated higher adoption of CE practices related to waste reduction, resource efficiency, and product design compared to firms with lower sales. Similarly, higher-revenue firms showed stronger internal pressure to adopt CE practices. Yet difficult-to-implement practices, such as waste-to-energy initiatives, were often overlooked in favor of easy-to-implement practices, such as recycling initiatives, unless leadership demonstrated high motivation. These results highlight the need for more guidance, enhanced leadership self-determination, and supportive policies to improve broader CE adoption among small manufacturers.